Los hidrocarburos en el Gobierno de Evo Morales: extractivismo nacionalista con presencia extranjera. (2016)
The aim of this article is to reflect on the actions of the government of Evo Morales in the national oil industry, considering its impact on the state link with transnational corporations and with Argentina and Brazil, in their capacity as energy partners. This study aims, through a bibliographical, documentary and statistical data analysis, to corroborate the assumption that despite the reformulation of energy contracts, the Movimiento al Socialismo has strengthened the reproduction of the extractive pattern where the state and foreign investment coexist and without achieving a significant progress in the industrialization of the sector.